TRANSFORMASI HUKUM SEBAGAI INSTRUMEN REKAYASA SOSIAL: ANALISIS FUNGSI RESPONSIF DALAM DINAMIKA MASYARAKAT INDONESIA KONTEMPORER - Kevy Listiana Fransisca Taneo; Fadil Masud; Marianus Bhau Rengga Bria; Argita Claudia Mone; Jenita Selan; Asri Laksenia Tamonob; Fadil Mas’ud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research adopts a qualitative design with a multi-sited ethnography strategy conducted cross-sectorally in three key domains agrarian and environmental conflicts, regulation of digital space and platform economy, informal economy and customs. The selection of these three domains is based on the consideration that they represent the most dynamic arenas of legal contestation in contemporary Indonesian society, where state law directly confronts alternative norms that exist in society. Multi sited ethnography allows researchers to trace how the phenomena of responsive law and legal pluralism operate in different geographical, social, and sectoral contexts, while remaining interconnected within the broader national legal system. This approach also facilitates in depth comparative analysis of variations in legal responses to social change across localities.